Morphometry and Cyclomorphosis in Daphnia middendorffiana from a Fishless Pond of the Southern Andes - Vega, Marina Soledad; Clausse, Alejandro (Taylor & Francis, 2000)
Fil: Vega, Marina Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica; Argentina